Dynamics of Electron–Hole Coulomb Attractive Energy and Dipole Moment of Hot Excitons in Donor–Acceptor Polymers - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Heterogeneous Structural Evolution of In–Zn–O Thin Films during Annealing - Moffitt, Stephanie L.; Cao, Chuntian; Van Hest, Maikel F. A. M.; Schelhas, Laura T.; Steinrück, Hans-Georg; Toney, Michael F. (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Do Lead Halide Hybrid Perovskites Have Hydrogen Bonds? - Ibaceta-Jaña, Josefa; Chugh, Manjusha; Novikov, Alexander S.; Mirhosseini, Hossein; Kühne, Thomas; Szyszka, Bernd; Wagner, Markus R.; Muydinov, Ruslan (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Photocatalytic Water Splitting Reaction Catalyzed by Ion-Exchanged Salts of Potassium Poly(heptazine imide) 2D Materials - Sahoo, Sudhir K.; Teixeira, Ivo F.; Naik, Aakash; Heske, Julian Joachim; Cruz, Daniel; Antonietti, Markus; Savateev, Aleksandr; Kühne, Thomas (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Microscopic Insights into Charge Formation and Energetics in n-Doped Organic Semiconductors - Dong, Chuan-Ding; Schumacher, Stefan (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Probing the Interactions of Immobilized Ruthenium Dihydride Complexes with Metal Oxide Surfaces by MAS NMR: Effects on CO2 Hydrogenation - Nguyen, Hoang-Huy; Li, Zheng; Enenkel, Toni; Hildebrand, Joachim; Bauer, Matthias; Dyballa, Michael; Estes, Deven P. (The Journal of Physical Chemistry C)
Homogeneous catalysts immobilized on metal oxides often have different catalytic properties than in homogeneous solution. This can be either activating or deactivating and is often attributed to interactions of catalyst species with the metal oxide surface. However, few studies have ever demonstrated the effect that close associations of active sites with surfaces have on the catalytic activity. In this paper, we immobilize H2Ru(PPh3)2(Ph2P)2N–C3H6–Si(OEt)3 (3) on SiO2, Al2O3, and ZnO and interrogate the relationship to the surface using IR, MAS NMR, 1H–31P HETCOR, and XAS spectroscopies. We found that while there are close contacts between the P atoms of the complex and all three metal oxide surfaces, the Ru–H bond only reacts with oxygen bridges on SiO2 and Al2O3, forming new Ru–O bonds. In contrast, complex 3 stays intact on ZnO. Comparison of the catalytic activities of our immobilized species for CO2 hydrogenation to ethyl formate showed that Lewis acidic metal oxides activate, rather than deactivate, complex 3 in the order Al2O3 > ZnO > SiO2. The Lewis acidic sites on the metal oxide surfaces most likely increase the productivity by increasing the rate of esterification of formate intermediates.
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Adsorption and Reaction of PbPc on Hydrogenated Epitaxial Graphene - Slawig, Diana; Gruschwitz, Markus; Gerstmann, Uwe; Rauls, Eva; Tegenkamp, Christoph (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Impact of Chlorine on the Internal Transition Rates and Excited States of the Thermally Delayed Activated Fluorescence Molecule 3CzClIPN - Streiter, Martin; Fischer, Tillmann G.; Wiebeler, Christian; Reichert, Sebastian; Langenickel, Jörn; Zeitler, Kirsten; Deibel, Carsten (The Journal of Physical Chemistry C)
Keywords: pc2-ressources

Toward Efficient Toxic-Gas Detectors: Exploring Molecular Interactions of Sarin and Dimethyl Methylphosphonate with Metal-Centered Phthalocyanine Structures - Aldahhak, Hazem; Powroźnik, Paulina; Pander, Piotr; Jakubik, Wiesław; Dias, Fernando B.; Schmidt, Wolf Gero; Gerstmann, Uwe; Krzywiecki, Maciej (The Journal of Physical Chemistry C)

Molecular Doping of PCPDT–BT Copolymers: Comparison of Molecular Complexes with and without Integer Charge Transfer - Dong, Chuan-Ding; Schumacher, Stefan (The Journal of Physical Chemistry C)
Keywords: pc2-ressources

Controlling the Electronic Contact at the Terpyridine/Metal Interface - Mennicken, Max; Peter, Sophia Katharina; Kaulen, Corinna; Simon, Ulrich; Karthäuser, Silvia (The Journal of Physical Chemistry C)
Keywords: pc2-ressources

Vibrational Properties of RbInSe2: Raman Scattering Spectroscopy and First-Principle Calculations - Guc, Maxim; Kodalle, Tim; Kormath Madam Raghupathy, Ramya; Mirhosseini, Hossein; Kühne, Thomas D.; Becerril-Romero, Ignacio; Pérez-Rodríguez, Alejandro; Kaufmann, Christian A.; Izquierdo-Roca, Victor (The Journal of Physical Chemistry C)

Stepwise Growth of Ruthenium Terpyridine Complexes on Au Surfaces - Peter, Sophia Katharina; Kaulen, Corinna; Hoffmann, Alexander; Ogieglo, Wojciech; Karthäuser, Silvia; Homberger, Melanie; Herres-Pawlis, Sonja; Simon, Ulrich (The Journal of Physical Chemistry C)

Vibrational Properties of RbInSe2: Raman Scattering Spectroscopy and First-Principle Calculations - Guc, Maxim; Kodalle, Tim; Kormath Madam Raghupathy, Ramya; Mirhosseini, Hossein; Kühne, Thomas; Becerril-Romero, Ignacio; Pérez-Rodríguez, Alejandro; Kaufmann, Christian A.; Izquierdo-Roca, Victor (The Journal of Physical Chemistry C)
RbInSe2 is attracting growing interest as a secondary semiconductor compound in Cu(In,Ga)Se2-based solar cells by virtue of the recent investigations on absorber post-deposition treatments with alkali metal salts that have resulted in significant efficiency improvements. However, the detection of the RbInSe2 phase on the surface of chalcopyrite absorbers is very challenging due to its nanometric thickness and the limited information available about its fundamental properties. In this context, this work expounds a detailed analysis of the vibrational properties of RbInSe2 that combines first-principle calculations with multiwavelength Raman scattering spectroscopy and provides a methodology for the detection and identification of very thin layers of this material employing solely optical measurements. As a result, here, we present the classification of the different vibrational modes together with the fingerprint Raman spectra of RbInSe2 thin films measured under five different excitations (close to and far from resonance). The employment of a 442 nm excitation wavelength is found to be the most adequate strategy for the detection and characterization of the RbInSe2 phase in view of its resonance with the band gap of the material and its low penetration depth. Additionally, the purity of the deposited thin films as well as the possible influence of the subjacent layers on the Raman spectra of the compound are also investigated by analyzing the presence of secondary phases and by measuring RbInSe2 thin films deposited onto Mo-coated soda-lime glass, respectively. These results set the basis for the future evaluation of the suitability of Raman spectroscopy as a fast and nondestructive characterization technique for the reliable identification and characterization of the nanometric layers of RbInSe2 in Cu(In,Ga)Se2-based solar cells.

Curved Polar Dibenzocoronene Esters and Imides versus Their Planar Centrosymmetric Homologs: Photophysical and Optoelectronic Analysis - Vollbrecht, Joachim; Wiebeler, Christian; Bock, Harald; Schumacher, Stefan; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry C)

Phase Transitions of Ice in Aqueous Salt Solutions within Nanometer-Sized Pores - Jantsch, Evelyn; Weinberger, Christian; Tiemann, Michael; Koop, Thomas (The Journal of Physical Chemistry C)
We examined the effect of CaCl2 and LiCl on ice melting in mesoporous silica (MCM-41 and SBA-15 silica). For that purpose, we determined the ice melting temperature in pores of various size (pore radii between 1.9 and 11.1 nm) in water and aqueous solutions up to high total solute molality (up to about 12 mol kg–1) using differential scanning calorimetry. We found that both electrolytes reduce the ice melting temperature within the pores. An exception is the melting of ice in the smallest pores, which does not seem to be affected by the presence of solutes, most likely owing to an exclusion of the ions from entering the pores. For all other pores, we observed that the ice melting temperature decreases as a function of pore size and electrolyte concentration. Using thermodynamic considerations as well as additional experimental data we developed a parametrization that can be used to predict the ice melting point as a function of pore size and total solute molality. For that purpose, we extended a formulation of the effective water activity of aqueous solutions under mechanical pressure toward its application in confinement and tested this new parametrization on literature data.

Enhanced Stability of Single-Layer w-Gallenene through Hydrogenation - Badalov, S. V.; Yagmurcukardes, M.; Peeters, F. M.; Sahin, H. (The Journal of Physical Chemistry C)

Switchable Plasmonic Holograms Utilizing the Electro-Optic Effect of a Liquid-Crystal Circular Polarizer - Atorf, Bernhard; Rasouli, Hoda; Mühlenbernd, Holger; Reineke, Bernhard J.; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry C)

Dependencies of the Adhesion Forces between TiO2 Nanoparticles on Size and Ambient Humidity - Laube, Jens; Dörmann, Michael; Schmid, Hans-Joachim; Mädler, Lutz; Colombi Ciacchi, Lucio (The Journal of Physical Chemistry C)
We study the variation of the adhesion forces between wet TiO2 nanoparticles as a function of their size and the ambient relative humidity. Combining all-atom molecular dynamics and capillary simulations we demonstrate that the linear scaling of the interparticle forces with the particle diameter, well established for microscopic and macroscopic particles, can be extended down to diameters of a few nm. At this size scale, however, the molecular nature of the water adsorbates dictates the adhesion forces both via solvation effects and influencing parameters of analytical capillary models such as the equilibrium particle–particle separation distance and the water/particle contact angle. Moreover, the water surface tension becomes considerably larger than the macroscopic bulk value due to combined effects of thin-film confinement and tight curvature, in a way that strongly depends on humidity and particle size. Taking these effects into proper account, classical capillary equations can be used to predict the interparticle forces even of the smallest particles considered here (4 nm), although the circular approximation fails to reproduce the distance at which the water meniscus breaks. Finally, the transition between the dominating effects at the nanoscopic scale and conventional capillary theory valid at microscopic size scales can be only rationalized if the presence of roughness asperities on the surface of the large particles is explicitly taken into account.

X-ray Spectroscopy of Thin Film Free-Base Corroles: A Combined Theoretical and Experimental Characterization - Aldahhak, Hazem; Paszkiewicz, M.; Allegretti, F.; Duncan, D. A.; Tebi, S.; Deimel, P. S.; Casado Aguilar, P.; Zhang, Y.-Q.; Papageorgiou, A. C.; Koch, R.; Barth, J. V.; Schmidt, Wolf Gero; et al. (The Journal of Physical Chemistry C)